Management of ß-thalassemia - Consensus and controversies! - Mamta V. Manglani; Pranoti S. Kini (Elsevier, 2017)
The mainstay of treatment of ß-Thalassemia major includes life-long regular packed red cell transfusions and iron chelation. With advances in understanding the molecular biology and its implications in the patients, newer modalities are now being explored to offer a better quality of life to transfusion dependent thalassemic patients. Improved safety of transfusions, newer chelator drugs and combination of chelators have improved outcomes in these patients. Amlodipine along with chelators may be a future option for preventing cardiac iron overload related complications. Drugs which improve HbF levels and thus ameliorate anemia such as hydroxyurea, butyrates azacytidine etc. have also been explored with little relief to transfusion dependent patients. HSCT, which is the only curative treatment available at present, has its own limitations as sibling donors may not be available to many. However, there has been extensive work done on improving outcomes with MUD and Haplo-identical HSCT in the recent times. Gene therapy using lentiviral vectors is also offering great hope to these children. Induced Pluripotent Stem Cells (iPSC) is a promising advance in the treatment of thalassemia. Several newer molecules targeting different pathophysiologic aspects are being explored and have met with good success. These include luspatercept, sotatercept, macrophage inhibition, JAK2 inhibition using ruxolitinib etc. Controversies regarding use of wheat grass and ESAs are relatively less worrisome. But use of thalidomide should be done with great caution. Despite its success reported in anecdotal reports, in the absence of adequate data with larger trials, its role in routine management of thalassemia syndromes remains to be ascertained.